The gut microbiota and aging: interactions, implications, and interventions - Gyriki, Despoina; Nikolaidis, Christos G.; Bezirtzoglou, Eugenia; Voidarou, Chrysa; Stavropoulou, Elisavet; Tsigalou, Christina (Frontiers in Aging, 2025)
The human microbiota, a complex ecosystem of microorganisms inhabiting various body sites, particularly the gut, plays a crucial role in maintaining health and influencing disease susceptibility. Dysbiosis, characterized by alterations in microbial composition and diversity, has been implicated in numerous diseases, including those associated with aging. This review examines the complex relationship between gut microbiota and aging, highlighting the age-associated gut microbiota alterations, the factors contributing to these changes, the links between microbiota and age-related diseases, and the potential of interventions targeting the microbiome to extend lifespan and improve health outcomes in the elderly. Further research is needed to unravel the intricate mechanisms underlying the interplay between the microbiome and aging, paving the way for innovative strategies to promote healthy aging.